A STUDY ON INCOME AND STANDARD-LIVING OF THE PEOPLE IN HALDIA, WEST BENGAL DUE TO INDUSTRIALIZATION - 1. Dinabandhu Maity , 2. Dr. G.L. Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This Study of the research aims in bringing forth reliable data about the effect of industrialization on the economic development of the place. It is also significant in bringing reliable data about the factors that influence the economy of Haldia and its impact on the GDP. Industrialization of Haldia has a drastic impact on the employment generation and has subsequently affected the Labouré market of the region. This shift in the nature of work has revolutionized the economy of this port city in West Bengal, India by offering new types of jobs and restructuring the work-related experiences of the people living in the area. Employment generation has been identified as one of the key factors that have propelled growth in Haldia, with the setting up of large industrial units, especially in the context of the petroleum refinery and chemical division and more so with the development of port infrastructure (Kumar et al. 2020). These large-scale industries have generated several direct employment opportunities, covering all categories of employees, ranging from the technical specialists to the semi-skilled and unskilled workers.